Translational surface coupling along a line with non-conforming meshes. (February 2022) - Nordas, Alexandros N.; Izzuddin, Bassam A.
Highlights: Systematic methodology for surface coupling along a line applicable to any 2D|3D FEs. Novel mortar-based line coupling element utilising augmented Lagrangian Multipliers. Novel translational coupling element for Reissner–Mindlin shell FE meshes. Systematic framework for modelling weld lines and eliminating transitional meshes. High-fidelity partitioned nonlinear analysis of large-scale metal structures. Abstract: In the modelling of large-scale metal structures, comprising plated components intersecting along weld lines, the meshing efficiency and flexibility are limited by the requirements of nodal alignment and compliance of element size, shape and edge orientation throughout the domain. Such limitations necessitate the use of complex transitional meshes in intersection regions and result in highly complex global mesh configurations. This paper presents an original and systematic methodology for surface coupling along an arbitrary 1D interface, which is applicable to any type of 2D and 3D FEs, and which provides a systematic framework for: (i) geometric modelling of weld lines; (ii) coupling of regions with different levels of discretisation detail or element types within a system; and (iii) domain partitioning problems involving computationally heterogeneous partitions. The strategy is based upon a novel coupling element formulation, which uses the fundamental principles of the mortar method and an augmented Lagrangian Multiplier optimisation approach. Particular consideration is given to an element formulation that enforces rigid translational coupling, which has been implemented for employment with co-rotational Reissner-Mindlin shell elements. Various numerical examples are presented to demonstrate the accuracy, versatility and substantial computational benefits of the developed methodology for modelling large-scale metal structural systems.